Intellectual property - Bagchi, J.K. (New Delhi, 2007)
This present books deals with "Intellectual Property" which was a critical area in the negotiations. As we all know before the WTO, this important area was dealth with by the Paris Agreement (1863), Berne Convention (1886), Madrid Agreement (1891), Universal Copyright Convention (1952), Rome Convention (1961), Geneva Convention (1961) & IPIC Treaty (1989).
Keywords: Intellectual property